التصنيع الأخضر كوسيلة للمحافظة على البيئة وتحقيق الأمن الغذائي - شنة, خديجة; شريفي, براهيم (جامعة الوادي - University of Eloued, 2023)
نهدف من خلال هذا البحث إلى معرفة مدى مساهمة الصناعة الخضراء في المحافظة على البيئة والحد من التلوث البيئي والمحافظة على تربة سليمة على المدى البعيد خاصة الزراعية منها، كونها تمثل الأساس الذي يتشكل منه الجزء الكبير من غذائنا. وتوصلنا إلى أن الصناعة الخضراء تعتبر خيارا استراتيجيا لتحقيق التنمية المستدامة، والقضاء على التلوث، كما أن الحرص على تشجيع المنشآت الصناعية على اتباع ممارسات التصنيع الأخضر يساعدها على تقليل التكاليف واستغلال الموارد المتاحة استغلالا أمثلا مما يجنبها مشكل هدر الطاقة وذلك من خلال إعادة تدوير النفايات، الأمر الذي يعمل على منع تلوث التربة والغذاء. We aim through this research to know the extent to which the green industry contributes to preserving the environment, reducing environmental pollution, and maintaining healthy soils in the long term, especially agricultural ones, as they represent the basis from which the large part of our food is formed. We concluded that the green industry is a strategic option to achieve sustainable development and eliminate pollution, and the concern to encourage industrial establishments to follow green manufacturing practices helps them reduce costs and make optimal use of available resources, thus avoiding the problem of wasting energy through waste recycling, the matter Which works to prevent soil and food contamination.
Green manufacturing as a means to preserve the environment and achieve food security
مقال
Keywords: التصنيع الأخضر ; البيئة ; التلوث ; الأمن الغذائي